Mimulus Stimpson, 1860, a junior synonym of Pugettia Dana, 1851 (Decapoda: Brachyura: Majoidea: Epialtidae) - Wicksten, Mary K.; Stachowicz, John J. (Zootaxa, 2013)
William Stimpson (1860) established Mimulus (Brachyura: Majoidea: Epialtidae), with a single species, M. foliatus. Rathbun (1894) placed the genus in synonymy with Pugettia Dana, 18951, but subsequent authors have considered Mimulus to be a valid genus. Genetic evidence and re-examination of the morphology indicate that M. foliatus belongs to a clade of majoid crabs consisting of species of Pugettia. We therefore consider Mimulus to be a junior synonym of Pugettia. We provide a list of all species of Pugettia